Kritik Budaya terhadap Krisis Identitas Jawa dalam Serat Jawa Tetep Jawa: Kajian Sosiologi Sastra Alan Swingewood - Laelika Rahma Agustin; Widodo Widodo; Dhoni Zustiyantoro (Universitas Hamzanwadi, 2026)
This study examines the forms of cultural criticism in Serat Jawa Tetep Jawa as a response to the shifting cultural identity of Javanese society. The text is a Javanese literary manuscript that reflects cultural criticism arising from changes in Javanese cultural identity, particularly the values that shape the concept of njawani (Javanese cultural character). Previous studies on social criticism have predominantly focused on modern novels, while classical Javanese manuscripts have received limited attention from the perspective of the sociology of literature. Therefore, this study aims to describe the forms of cultural criticism contained in Serat Jawa Tetep Jawa. This research employs a qualitative descriptive approach using content analysis and is grounded in Alan Swingewood’s sociology of literature. This perspective regards literary works as reflections of social structures and expressions of the collective consciousness of society, making it appropriate for analyzing cultural criticism. The research object is Serat Jawa Tetep Jawa based on the transliterated and translated manuscript prepared by Pramestian (2021). Data were collected through library research, while data analysis consisted of text identification, categorization of cultural criticism, and interpretation of meanings within the context of Javanese culture. The findings reveal that the manuscript predominantly criticizes the erosion of Javanese identity, the transformation of traditional Javanese attire, and the distortion of moral values driven by social status. These findings demonstrate that the manuscript functions not only as a medium of social reflection but also as an instrument of cultural control in preserving Javanese cultural values.